Assessing the Impact of Culture: A Systematic Analysis of Culture-Based Interventions and Evaluations - Austin, Eric; Ward, Nic; Otto, Jay; Green, Kelly; Watson, Holly (Frontiers in Future Transportation, 2022)
Over the last twenty years, transportation agencies have added culture-based approaches to the existing education, engineering, and enforcement strategies being used as a means of reducing traffic related injuries and fatalities. Despite this increased interest, there have been comparatively few evaluations of these interventions. At the same time, many other organizational types have adopted culture-based strategies either to improve safety or to enhance other elements of organizational performance. In aggregate, the evaluations of culture-focused interventions across a range of settings offer an untapped body of information about the models of culture being leveraged to affect change, the intervention strategies used to impact culture, the impacts of these strategies, and more. The research presented here used a systematic analysis of published, peer-reviewed evaluations of culture-based interventions designed to enhance traffic safety, and safe workplaces and practices more broadly, in order to more comprehensively understand the current state and impacts of culture-based theory and practices. This study seeks to build a clearer picture of the presence and robustness of current models of culture being utilized, as well as what evaluation strategies and designs are being used to evaluate culture-based initiatives, and further, what the robustness of the existing models and evaluations reveals about the efficacy of the original, culture-based interventions. Lastly, this analysis includes a preliminary examination of links between culture-based initiatives and systems theory/thinking, in an effort to identify conceptual ties between and/or empirical evidence supporting a relationship between the “Safe System” approach and traffic safety culture or other culture-based efforts. It is hoped that with a clearer understanding of the status of the field, it will be possible to make further progress in crafting, assessing, and refining theoretically robust and empirically grounded efforts to advance the efficacy of traffic safety culture and safe systems approaches.